Monodispersed Ce(IV)-Gd(III)-Eu(III) oxide phosphors for enhanced red emission under visible excitation - Sorbello, Cecilia (2013)
A family of Ce0.95−xGdxEu0.05(OH)CO3·H2O monodispersed spherical particles of ca. 200 nm with 0 ≤ x ≤ 0.95 was obtained by the urea homogeneous alkalinization method. These precursors were decomposed at 1273 K under an air atmosphere, resulting in ternary spheroidal phosphors obeying the general formula Ce0.95−xGdxEu0.05O1.975−x/2. Samples with 0.57 ≤ x ≤ 0.95 exhibit a c-type (Ia3) structure related to the Gd2O3 lattice, while a Fm3m-type (CeO2) one was found for 0 ≤ x ≤ 0.19. For both ternary families, the partial substitution of host cations dramatically decreases the efficiency of the ligand to metal charge transfer (LMCT) based emission, with respect to their binary end members. In contrast, the emission obtained from direct excitation of Eu(III) with visible light is enhanced. For both structures, the binary Ce(IV)-Gd(III) host improved emission with respect to Gd0.95Eu0.05O1.5 and Ce0.95Eu0.05O1.975 samples, achieving an optimum value for the sample Ce0.23Gd0.71Eu0.05O1.6 with a Ia3 structure.